Surface roughness evaluation of additive manufactured components using fiberscopes - Seah, Benjamin Yan Hui (Nanyang Technological University, 2024)
Additive Manufacturing (AM) processes have revolutionized traditional manufacturing methods, offering unique advantages in terms of design flexibility, rapid prototyping, and material efficiency. Surface roughness is a crucial factor in engineering industries, especially in aerospace and automobile as it can affect factors such as friction, wear resistance and material fatigue life. Several methods are available to measure the surface roughness of the components, but most of them have limited ability to measure the surface roughness of complex structures. There is an urgent need for a flexible probe for measuring surface structures of complex structures like internal channels of engines is necessary. This work reports a method to measure the surface roughness of complex components by using a flexible fiberscope. A 0.3 mm diameter fiberscope is used to collect the speckle patterns created by laser from the samples. The fiberscope contains 1600 picture elements which gives a pixel to pixel spacing of 3.3 µm. Multiple image processing algorithms are used to remove the comb structures formed by the picture elements of the fiberscope. The surface roughness of the samples is estimated by angular speckle correlation. Standard comparator plates are used to calibrate the system, and the calibration graph is plotted for different surface roughness values. The surface roughness of unknown samples and complex channels is estimated by using the calibration curve. This method provides an accurate measurement of the surface roughness of the internal channels, which are not accessible by conventional measurement techniques.